The Implementation of Student Exchange Program in Higher Education: The Study in a University in Indonesia - Lodya Sesriyani; Saiful Anwar; Rusmaini Rusmaini (STAI Hubbulwathan Duri, 2022)
This study aimed to analyze the implementation of Program Merdeka Belajar Kampus Merdeka (MBKM) which was implemented in one of the private universities in Indonesia. The focus of this research was the implementation of Program Pertukaran Mahasiswa Merdeka (PMM), where in this program students temporarily exchange to run courses at partner universities. This research is expected to answer what must be evaluated in the program Pertukaran Mahasiswa Merdeka (PMM). The subjects in this study were all students in the PMM program activities in the Perkembangan Peserta Didik' course. Observations were made for nine meetings conducted online both on Google meet and on the Spada Dikti dashboard. There were sixteen students whose activities were observed and two lecturers who taught courses. During the observation, information was found regarding timeliness of students and lecturers in starting and ending lectures, students’ discipline when collecting individual and group assignments, signal problems that often occur, effectiveness of the Dikti dashboard, to the final conversion of students' grades at their respective universities.